IMPLEMENTASI METODE YANBU’A DALAM MENINGKATKAN KEMAMPUAN BACA AL-QUR’AN DIKALANGAN LANSIA DI TPQ ANWARUL QUR’AN GEDANG TAMBAKREJO JOMBANG - Rohimah, Yuhanidz Habibatur; Surur, Shobihus (Education, Learning, and Islamic Journal, 2020)
Abstract: The Yanbu'a method is a method of reading, writing, and memorizing the Qur'an whose writing is adapted to the Ottoman Rasm. Reading the Qur'an is seeing and living what is written in the Qur'an. The Elderly is an age that is approaching the end of the human life cycle in the world starting in the 60s until the end of life. The focus of the problem in this study are: (1) How is the application of the Yanbu'a Method among the elderly at TPQ Anwarul Qur'an Gedang Tambakrejo Jombang, (2) How is the ability to read the Qur'an among the elderly at TPQ Anwarul Qur' an Gedang Tambakrejo Jombang, (3) What are the supporting and inhibiting factors for the application of the Yanbu'a method in improving the ability to read the Qur'an among the elderly at TPQ Anwarul Qur'an Gedang Tambakrejo Jombang. The research in this thesis uses qualitative research, while the approach used in this study uses a case study approach, the data collection techniques used are observation, interviews, and documentation. The results of the study show (1) the application of the Yanbu'a Method Among the Elderly at TPQ Anwarul Qur'an Gedang Tambakrejo Jombang, the learning activities are carried out 2 times a week, namely on Saturdays and Sundays. The application of the Yanbu'a method at the Anwarul Qur'an Elderly TPQ begins with volume 1 for all elderly participants, both those who are fluent in reading and those who are not fluent in reading. The difference in learning between elderly participants and children is only in the basic method of learning. In the Yanbu'a method, it is systematically arranged according to its level from volumes, I, II, III, IV, V, VI, and VII. Each volume has a different purpose according to its learning abilities. (2) The ability to read the Qur'an at the Anwarul Qur'an Elderly TPQ is different. Some are already smooth and some are just starting from the basics. The reading fluency of the elderly depends on their own reading ability. The more often you hone your own reading, the better the quality of your reading will be. (3) Several factors supporting the application of the Yanbu'a method in improving the ability to read the Koran among the elderly include creating a sense of pleasure among the elderly and adding positive activities for the elderly. While the inhibiting factors are the time clash between the activities of the cottage and the TPQ, as well as the disease of the elderly who are prone to occur at a young age.